(untitled) (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2024)
Franchising, being a widely adopted business strategy on a worldwide scale, is dependent on complex legal structures that regulate the interactions between franchisors and franchisees. This article presents an informative overview of franchising contracts and the associated legal issues, focusing on a comparative analysis between the United Kingdom (UK) and the United States of America (US). This paper aims to provide insight into the structure, regulation, and enforcement of franchising contracts in two different jurisdictions. Through careful examination, the specific characteristics of both jurisdictions will be highlighted. This article examines franchising contracts and their legal intricacies in two notable legal systems.